Design And Simulation of a Hexagonal High-Gain MIMO Patch Antenna For 5G Applications - Borel, Touko Tcheutou Stephane; Priyadarshini, Rashmi (International Journal of Membrane Science and Technology, 2023)
View of the technological evolution and the problems encountered by the world, researchers are obliged to find solutions, particularly researchers in the field of antennas. This article has been devoted to the design and study of a hexagonal dual-band MIMO patch antenna for Satellite and 5G applications. Several parameters have been studied, we can quote among other things the gain, the bandwidth, the radiation diagram, the directivity, and the distribution of the electric field E. To achieve these studies and find optimal solutions, several designs have been made like the design of a simple hexagonal patch antenna, and, in the end, the proposed antenna is a MIMO with a hexagonal shape and 2 feeding ports. The proposed antenna operates at 25 GHz as the central frequency. The obtained ECC (envelope correlation coefficient) value is less than 0.006 for the entire operating bandwidth, which satisfies the standard value criteria of less than 0.5 and indicates minimal isolation between the antenna arrays. The values of the gain and the maximum directivity of the antenna obtained are respectively 8.12 dB and 8.37 dB, which gives us an efficiency of the antenna at 97.01% with high isolation > 25 dB. The results are found to be sufficient for the device to be used for mm-wave 5G MIMO applications. Additional MIMO performance metrics, such as the channel capacity loss (CCL), diversity gain (DG), and total active reflection coefficient (TARC), are evaluated. All this work has been done using HFSS 15 as software.